(untitled) (Research, Society and Development, 2022)
The skin aging factors, especially facial, is accelerated by extrinsic and intrinsic factors, such as sun, weather, food, among others. The signs of aging and facial appearance are linked to muscle action, loss of bone support, sagging skin and decreased volume of facial fat compartments. For the treatment of aging skin, there are some filler technologies that include collagen biostimulators that promote biocollagenase. Thus, the objective of this study is to carry out a literature review regarding the action of collagen biostimulating substances in facial harmonization, making a comparative analysis between these substances. In this literature review, twenty publications were selected that focused on the use of collagen biostimulators. At the end of the study, it was possible to conclude that the collagen biostimulators most used today are: poly-l-lactic acid, calcium hydroxyapatite and polycaprolactone. Both have common characteristics, as they are biocompatible and synthetic, which act in the production of collagen by the body, and the difference between them is only in the clinical indication for the treatment.